Development of Interactive Infographic Learning Multimedia on Study Methodology Study Course of Economic Education Program of Mulawarman University - Sudarman; Sugeng; Hairullah (JPP (Jurnal Pendidikan dan Pembelajaran), 2018)
This study aims to develop an interactive multimedia infographic learning based on HTML5, as well as test its feasibility and quality. The method used in this research is research and development (R&D) with the DDDE development method (Decide, Design, Development, Evaluation). This research was conducted at the Economic Education Study Program FKIP Mulawarman University. The results of this study indicate that: (1) Multimedia interactive infographic learning developed based on HTML5 is suitable for offline use. (2) Multimedia interactive interactive infographic learning in research methodology courses have been declared feasible by experts of research methods teaching materials with an average value of 4.10, multimedia learning experts with an average value of 4.15, and multimedia practitioners of learning with an average value of 4.66. (3) Multimedia interactive infographic learning in research methodology courses has been tested to have good quality in individual trials with an average value of 3.83, in small group trials with an average value of 4.23, and in field trials with an average value of 4.22.